Profiling firms conducting international electronic commerce: an exploratory analysis. (29th December 2005) - Leger, Pierre-Majorique; Cassivi, Luc
Very few empirical studies have examined the dual phenomenon of electronic and international commerce. The goal of this exploratory paper is to develop a preliminary understanding of firms that behave similarly in terms of both internationalisation and electronic commerce usage. Building on the contingency theory and the resource-based view of the firm, this paper reveals five configurations of firms according to their level of electronic and international commerce usage. In order to refine the configuration profiles, the five groups are then compared over four contingency factors. The group of firms that is highly involved in both international trade and electronic commerce: 1. relies proportionally more on logistical aspects related to the physical nature of the offering than the other groups; 2. deals with fewer individual customers than the groups specialising in local markets; 3. is composed of smaller firms compared to international non-electronic-commerce firms. The paper concludes with recommendations for future research on international electronic commerce.